Carbon Nanolights in Piezopolymers are Self‐Organizing Toward Color Tunable Luminous Hybrids for Kinetic Energy Harvesting. Issue 8 (30th January 2020) - He, Xuebing; Wang, Chuanfeng; Huang, Xi; Jin, Long; Chu, Xiang; Xie, Meilin; Nie, Yiwen; Xu, Yali; Peng, Zhou; Zhang, Chaoliang; Lu, Jun; Yang, Weiqing
Abstract: Herein, an all‐solid‐state sequential self‐organization and self‐assembly process is reported for the in situ construction of a color tunable luminous inorganic/polymer hybrid with high direct piezoresponse. The primary inorganic self‐organization in solid polymer and the subsequent polymer self‐assembly are achieved at high pressure with the first utilization of piezo‐copolymer (PVDF‐TrFE) as the host matrix of guest carbon quantum dots (CQDs). This process induces the spontaneous formation of a highly ordered, microscale, polygonal, and hierarchically structured CQDs/PVDF‐TrFE hybrid with multicolor photoluminescence, consisting of very thermodynamic stable polar crystalline nanowire arrays. The electrical polarization‐free CQDs/PVDF‐TrFE hybrids can efficiently harvest the environmental available kinetic mechanical energy with a new large‐scale group‐cooperation mechanism. The open‐circuit voltage and short‐circuit current outputs reach up to 29.6 V cm −2 and 550 nA cm −2, respectively. The CQDs/PVDF‐TrFE–based hybrid nanogenerator demonstrates drastically improved durable and reliable features during the real‐time demonstration of powering commercial light emitting diodes. No attenuation/fluctuation of the electrical signals is observed for ≈10 000 continuous working cycles. This study may offer a new design concept for progressively but spontaneously constructing novel multiple self‐adaptive complex inorganic/polymer hybrids that promise applications in the next generation of self‐powered autonomous optoelectronic devices. Abstract : The sequential self‐organization and self‐assembly of carbon nanolights in solid piezopolymers, progressing from nano‐ to micro‐ to macroscale, lead to the spontaneous construction of a large number of highly ordered multicolor luminous nanogenerators with an increased degree of complexity. They work with a new large‐scale group‐cooperation mechanism to harvest kinetic mechanical energy, and demonstrate ultrahigh and superstable direct piezoresponses in long‐term operation.